SAT0182 Improvement in Measures of Depressed Mood and Anhedonia, and Fatigue, In a Randomized, Placebo-Controlled, Phase 2 Study of Sirukumab, A Human Anti-Interleukin-6 Antibody, In Patients with Rheumatoid Arthritis. (9th June 2015) - Hsu, B.; Wang, D.; Sun, Y.; Salvadore, G.; Singh, J.; Curran, M.; Caers, I.; Drevets, W.; Wittenberg, G.; Chen, G.
Abstract : Background: Interleukin-6 (IL-6) is among the known neuroactive cytokines involved in stress coping and neuronal plasticity. Clinical and preclinical studies suggest a role for IL-6 in the pathophysiology of depression; it is unclear whether peripheral anti-IL-6 treatment can directly alleviate depressive symptoms. Depressive symptoms and fatigue commonly affect RA patients, particularly those with high disease activity. Objectives: To assess the effects of sirukumab, a human IL6 antibody, on measures of depressed mood and anhedonia, and fatigue from a Ph2 trial in patients with active RA. Methods: This was a post-hoc analysis of the SF-36 Mental Health and Vitality domain items from a Ph2, multicenter, randomized, double-blind, placebo-controlled study evaluating efficacy and safety of 4 dose regimens of sirukumab (25mg q4wks up to 100mg q2wks) administered SC in patients with active RA despite MTX. Serum CRP ≥10mg/L was required for enrollment, and history of an uncontrolled psychiatric or emotional disorder that was of sufficient severity to interfere with study participation was excluded. Patients using anti-depressants were excluded from analysis. Patients were grouped by presence or absence of prevalent depressed mood and anhedonia (PDMA) at entry, defined as self-reported depressed mood and anhedonia on the SF-36 with >1 item designated "most of the time" and the other at least "some of the time" for 4wks. Sirukumab treatment was defined as receiving any sirukumab regimen. Change from baseline in PDMA and fatigue at wk12 were analyzed unadjusted and adjusted for baseline and wk12 DAS28-CRP score; to investigate the relationship between depressive symptoms improvement and RA clinical response, change in PDMA symptoms was also investigated separately in ACR50 responders and non-responders Results: At entry, about 26% of patients were classified as having PDMA. This group also experienced significantly more fatigue and nervousness than those without PDMA. The severity of PDMA symptoms in this group was not significantly correlated with RA chronicity or severity, or with baseline serum levels of inflammatory biomarkers. Clinical efficacy of sirukumab on RA disease symptoms as measured with the DAS28-CRP occurred in patients with and without PDMA at entry. Patients in the PDMA group receiving sirukumab but not PBO achieved significant improvements at wk12 in PDMA symptoms (p=0.0006), and fatigue (p=0.0157). In patients with PDMA, significant improvements on PDMA symptoms upon sirukumab treatment, but not PBO, were observed in both ACR50 responders (p=0.0024) and non-responders (p=0.0014). In patients with PDMA treated with sirukumab, baseline soluble IL-6 receptor (sIL-6R) level significantly correlated with improvement at wk12 in PDMA symptoms (Spearman r=0.44, p=0.015). Conclusions: These novel findings link IL-6 signaling pathway dysregulation to depressive symptoms and fatigue, and suggest that peripheral anti-IL-6 treatment can improve depressive symptoms in RA patients independently of clinical response. References: Hodes GE et al, PNAS 2014;111(45):16136-16141. Smolen JS et al, ARD 2014;73:1616-1625. Disclosure of Interest: B. Hsu Employee of: Janssen, D. Wang Employee of: Janssen, Y. Sun Employee of: Janssen, G. Salvadore Employee of: Janssen, J. Singh Employee of: Janssen, M. Curran Employee of: Janssen, I. Caers Employee of: Janssen, W. Drevets Employee of: Janssen, G. Wittenberg Employee of: Janssen, G. Chen Employee of: Janssen